A new form of communication for the citizen Senior: Facebook - Páscoa, Gina Maria Gouveia (2015)
This paper presents a research with senior citizens and their interactions with the digital social network Facebook. The main objective was to understand the contribution of Facebook in promoting active ageing. It is a qualitative case study in a computer class at a university of the third age of Castelo Branco (Portugal), attended by a group of 13 seniors. The results showed that Facebook is used to communicate, combat loneliness and as a way of lifelong learning.